Analisis Keterampilan Berpikir Kritis Peserta Didik Kelas VIII di Kecamatan Bantimurung - Mutiara Zahirah; Muh. Tawil; Rifda Nur Hikmahwati Arif (Universitas Negeri Makassar, 2025)
This study aims to determine how high the level of critical thinking skills of class VIII students in Bantimurung District. This research is a descriptive survey research using a quantitative approach. The population in this study were students of grade VIII junior high school in Bantimurung District, totaling 400 students from 3 schools, namely SMPN 4 Bantimurung, SMPN 22 Bantimurung and SMPN 39 Satap Leang-leang. Sampling used the Random Sampling technique and billed the number of samples using the slovin formula, namely 200 students. The research instrument was in the form of 20 multiple choice questions. Based on the results of data analysis it is known that the level of critical thinking skills of class VIII students in Bantimurung District is 66% which is included in the high category.